Religious-ideological Bases of Islamic Solidarity - Mammadov, Elvusal (Scholarya Demo Journal of Ruby, 2019)
Since the end of the last century, Islamic solidarity has been an actuality of non-religious ideologies in the Muslim world nationalism and socialism, especially after insolvency of efforts to unite Arabs. The main platform of this model of solidarity is historically formed by Islam, which has ensured the unified cultural religious, political-economic and social integrity of ArabMuslim peoples in a wide zone Muslim geography. Because Islam is a common value of Muslim countries, a basic element of the common history and culture that unites them both in the past and in the present. Both the liberal and socialist ideologies applied to the Arab-Muslim world from the 30’s of the last century in order to solve political and ideological problems were artificial and productive, as well as the role of Islam as the main element in the formation of the identity of this geography made it necessary from the Islamic point of view. From this point of view, the Islamic standpoint has principles and values that reflect the historical experience and play the role of both base and promoting mechanism in unity and solidarity. If these principles and values are based in the present period, Islamic solidarity can yield its results. This point of view in the study is also justified by the fact that spiritual and moral values are needed for the individual and society; the creation of a cultural and social system based on the successful harmony of material and spiritual life is a requirement of the day; capitalism based on individualism, socialism exiting from collectivism does not demonstrate a balanced attitude towards individual and society issues. The article presents the concepts of Ummah and Brotherhood as the religious-ideological basis of Islamic solidarity.